The beginning of a friendship: Teaching individuals with autism to identify shared interests. Issue 4 (15th September 2022) - Hood, Stephanie A.; Gopez, Jesey M.; Fallon, Maya J.; Byczynski, Francesca A.; Aquino, Sylvia C.; Monroy, Stephanie
Abstract : Individuals with conversation skill deficits often have difficulties discriminating cues of interest and uninterest from their conversation partner(s). We used behavioral skills training (BST) to teach 3 individuals with autism spectrum disorder to converse about the conversation partner's topics of interest, initiate strategic preferred topics to identify shared interests after indices of uninterest, and end the conversation. We assessed generality of each skill across conversation partners and ratings of social acceptability. We replicated previous research on BST producing robust increases in following the conversation, shifting the topic of conversation, and ending the conversation. In addition, all participants learned to categorize shared interests. We observed overall high levels of generality across following, shifting, and ending the conversation with all conversation partners. However, for 2 out of the 3 participants the inclusion of rules was necessary to promote the generality of the intraverbal categorization response. We discuss the implication of these findings for clinical practice and future research.